Isolation and Characterization of Phosphate Solubilizing Bacteria from Upland Rice Cultivation Areas in Bangka Regency - Kartika, Kartika; Munif, Abdul; Palupi, Endah Retno; Ilyas, Satriyas; Suhartanto, Muhamad Rahmad (Journal of Tropical Biodiversity and Biotechnology, 2024)
The availability of phosphorus (P) in ultisol acid soils presents a significant challenge due to its attachment to aluminum (Al) or iron (Fe) compounds. A potential solution to address this issue is the utilization of phosphate solubilizing bacteria (PSB). Therefore, this study aimed to analyze the potential of PSB originating from upland rice cultivation on ultisol soils. The bacterial isolates were obtained from soil samples taken from the rhizosphere area and root tissue of upland rice plants cultivated in Payabenua and Saing Villages, Bangka Regency. The pathogenicity testing encompassed hypersensitivity and hemolysis tests, while the P solubilization included the evaluation of the phosphate solubilizing index (PSI) and P dissolution. Subsequently, the selected isolates were subjected to phosphatase enzyme and organic acid content assessment. The results showed a total of 120 isolates, predominantly distributed in the Payabenua area and primarily consisting of endophytic bacteria. Among the six selected isolates, genus Burkholderia dominated four isolates, while the remaining isolates belonged to genus Serratia. Furthermore, in Burkholderia vietnamiensis, the solubility value of P in AlPO4 and Ca3(PO4)2 liquid media exhibited a range of 0.0013 to 0.0344% and 0.0008 to 0.1842%, respectively.